FACTORS ASSOCIATED WITH UNDERWEIGHTS AMONG CHILDREN OF 6-59 MONTHS AGE IN MIESSO DISTRICT, OROMIA, ETHIOPIA (Applied Biological Research, 2023)
Children are most exposed to under nourishment because of high dietary  requirements for their growth and development. The present study was  aimed to determine the prevalence of underweight children in age group of  6-59monthsinMeisso district, Oromia (Ethiopia) and identify the associated  factors responsible for it. A community based cross sectional study was  conducted on 296 children. The data was collected by using a well structured pretested questionnaire. Anthropometric measurements of  children were taken to assess their nutritional status. Generalized ordered  logit model, proportional odds model and partial proportional odds model were compared and finally the partial proportional odds model was taken  as the best model for current study to identify the factors associated with  the nutritional status of children. The study showed that underweight was a  serious problem in Miesso district with the prevalence of severe  underweight as 24.0% and those of mild underweight as 26.7%. The  predictors significantly related to the child nutritional status were sex, age,  household’s food security status and the toilet using status of family, since  the child malnutrition in the district was very highly prevalent continuous  nutrition supervision and special attention to severely malnourished  children is necessary to overcome malnutrition problem.
Keywords: Miesso; malnutrition; partial proportional odds models; underweight; weight for age